Astragaloside IV protects RGC-5 cells against oxidative stress - Hao, Ming (Neural Regen Res, 2018)
Astragaloside IV is the main active compound of Astragalus membranaceus. Astragaloside IV has strong anti-oxidative activities and protective effects against progression of peripheral neuropathy. In this study, we determined whether astragaloside IV protects retinal ganglion cells (RGC) from oxidative stress injury using the rat RGC-5 cell line. Hydrogen peroxide (H(2)O(2)) was used to induce oxidative stress injury, with the protective effect of astragaloside IV examined. Cell Counting Kit-8 and 4′,6-diamidino-2-phenylindole staining showed that astragaloside IV increased cell survival rate and decreased apoptotic cell number. Flow cytometry showed that astragaloside IV decreased H(2)O(2)-induced reactive oxygen species levels. While laser confocal microscopy showed that astragaloside IV inhibited the H(2)O(2)-induced decrease of mitochondrial membrane potential. Western blot assay showed that astragaloside IV reduced cytochrome c release induced by H(2)O(2), inhibited Bax and caspase-3 expression, and increased Bcl-2 expression. Altogether, these results indicate that astragaloside IV has potential protective effects against H(2)O(2)-induced oxidative stress in retinal ganglion cells.